ОСНОВНІ АСПЕКТИ ОСВІТНЬОЇ ЄВРОІНТЕГРАЦІЇ УКРАЇНИ (Педагогіка вищої та середньої школи, 2008)
The given article is devoted to the analysis of role of education in society. Attention on its anal is is in modern terms is accented, from this industry not only the future of man, citizen but also states depends on the whole. Basic principles of reformation of Ukrainian educational industry in the conditions of eurointegration are considered. In the article is heaved up a question about some disparities of European educational requirements to the traditional postulates of the system Ukrainian education.